2020
DOI: 10.1177/1474515119900075
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ knowledge on cardiopulmonary resuscitation correlated with return of spontaneous circulation rates after in-hospital cardiac arrests: A multicentric study between university hospitals in 12 European countries

Abstract: Background: In-hospital cardiac arrest is a major cause of death in European countries, and survival of patients remains low ranging from 20% to 25%. Aims: The purpose of this study was to assess healthcare professionals’ knowledge on cardiopulmonary resuscitation among university hospitals in 12 European countries and correlate it with the return of spontaneous circulation rates of their patients after in-hospital cardiac arrest. Methods and results: A total of 570 healthcare professionals from cardiology, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…For instance, a stark 91% of doctors had reportedly never performed CPR in Karachi, Pakistan, with a majority unfamiliar with correct compression rates, emphasizing the deficiency in practical BLS application (Majid et al). Despite these gaps, a generally positive attitude towards engaging in CPR and AED training and community projects was noted among participants, resonating with literature that underscores the healthcare community's recognition of BLS's value (11,18). Interestingly, our study found no significant impact of gender or experience on BLS knowledge and practice, aligning with other research findings indicating that these demographic factors do not necessarily correlate with BLS proficiency (13).…”
Section: Discussionsupporting
confidence: 81%
“…For instance, a stark 91% of doctors had reportedly never performed CPR in Karachi, Pakistan, with a majority unfamiliar with correct compression rates, emphasizing the deficiency in practical BLS application (Majid et al). Despite these gaps, a generally positive attitude towards engaging in CPR and AED training and community projects was noted among participants, resonating with literature that underscores the healthcare community's recognition of BLS's value (11,18). Interestingly, our study found no significant impact of gender or experience on BLS knowledge and practice, aligning with other research findings indicating that these demographic factors do not necessarily correlate with BLS proficiency (13).…”
Section: Discussionsupporting
confidence: 81%
“…Leaving this to the simulated or observational training offered by individual trusts creates a lottery where we risk students and foundation year doctors progressing to further training feeling underprepared for medical emergencies. This is supported by evidence from a large multicentre study, which found that better knowledge of advanced life support resulted in improved outcomes for patients experiencing in-hospital cardiac arrests 6…”
mentioning
confidence: 81%
“…This finding was similar to Meert's report, in which an inverse correlation between the dose of epinephrine and 12-month survival was reported ( 17 ). Prior studies have proved that mortality increased as the CPA and CPR persisted ( 3 , 9 , 18 ). In our opinion, the poor outcomes were actually due to severe illnesses, which caused prolonged CPA and CPR, and clinicians had to administer epinephrine repeatedly.…”
Section: Discussionmentioning
confidence: 99%